Analyzing the clinical actionability of germline pharmacogenomic findings in oncology. Issue 14 (9th May 2018) - Wellmann, Rebecca; Borden, Brittany A.; Danahey, Keith; Nanda, Rita; Polite, Blase N.; Stadler, Walter M.; Ratain, Mark J.; O'Donnell, Peter H.
Abstract : BACKGROUND: Germline and tumor pharmacogenomics impact drug responses, but germline markers less commonly guide oncology prescribing. The authors hypothesized that a critical number of clinically actionable germline pharmacogenomic associations exist, representing clinical implementation opportunities. METHODS: In total, 125 oncology drugs were analyzed for positive germline pharmacogenomic associations in journals with impact factors ≥5. Studies were assessed for design and genotyping quality, clinically relevant outcomes, statistical rigor, and evidence of drug‐gene effects. Associations from studies of high methodologic quality were deemed potentially clinically actionable, and translational summaries were written as point‐of‐care clinical decision support (CDS) tools and formally evaluated using the Appraisal of Guidelines for Research and Evaluation (AGREE) II instrument. RESULTS: The authors identified germline pharmacogenomic results for 56 of 125 oncology drugs (45%) across 173 publications. Actionable associations were detected for 12 drugs, including 6 that had germline pharmacogenomic information within US Food and Drug Administration labels or published guidelines (capecitabine/fluorouracil/dihydropyrimidine dehydrogenase [ DPYD ], irinotecan/uridine diphosphate glucuronosyltransferase family 1 member A1 [ UGT1A1 ], mercaptopurine/thioguanine/thiopurine S‐methyltransferase [ TPMT ], tamoxifen/cytochrome P450 [CYP] family 2 subfamily D member 6 [ CYP2D6 ]), and 6 others were novel (asparaginase/nuclear factor of activated T‐cells 2 [ NFATC2 ]/human leukocyte antigen D‐related β1 [ HLA ‐ DRB1 ], cisplatin/acylphosphatase 2 [ ACYP2 ], doxorubicin/adenosine triphosphate‐binding cassette subfamily C member 2/Rac family small guanosine triphosphatase 2/neutrophil cytosolic factor 4 [ ABCC2/RAC2/NCF4 ], lapatinib/human leukocyte antigen DQ α1 [ HLA‐DQA1 ], sunitinib/cytochrome P450 family 3 subfamily A member 5 [ CYP3A5 ], vincristine / centrosomal protein 72 [ CEP72 ]). By using AGREE II, the developed CDS summaries had high mean ± standard deviation scores (maximum score, 100) for scope and purpose (92.7 ± 5.1) and rigour of development (87.6 ± 7.4) and moderate yet robust scores for clarity of presentation (58.6 ± 25.1) and applicability (55.9 ± 24.6). The overall mean guideline quality score was 5.2 ± 1.0 (maximum score, 7). Germline pharmacogenomic CDS summaries for these 12 drugs were recommended for implementation. CONCLUSIONS: Several oncology drugs have actionable germline pharmacogenomic information, justifying their delivery through institutional pharmacogenomic implementations to determine clinical utility. Cancer 2018;124:3052‐65. © 2018 American Cancer Society . Abstract : Results from a critical analysis of germline pharmacogenomic findings are reported for 125 oncology drugs, asserting that clinically actionable associations exist for 12 different drugs, 6 of which are not represented in US Food and Drug Administration labels or published guidelines. By using a rigorous analysis based on the Appraisal of Guidelines for Research and Evaluation (AGREE II) methodology, the authors have developed implementation for point‐of‐care clinical decision support summaries to translate germline results into the care of oncology patients.